Geographic and Ethnic Variations in Radiographic Disability Thresholds: Analysis of North American and Japanese Operative Adult Spinal Deformity Populations. Issue 6 (June 2016) - Ames, Christopher; Gammal, Isaac; Matsumoto, Morio; Hosogane, Naobumi; Smith, Justin S.; Protopsaltis, Themistocles; Yamato, Yu; Matsuyama, Yukihiro; Taneichi, Hiroshi; Lafage, Renaud; Ferrero, Emmanuelle; Schwab, Frank J.; et al.
Abstract : BACKGROUND: Thresholds for spinal pelvic parameters in adult spinal deformity (ASD) were previously defined in North American patients and are commonly used to guide surgical planning. However, it is unclear whether these same threshold parameters can be more widely applied in other geographic regions and in other ethnicities. OBJECTIVE: To evaluate the variation in the radiographic disability thresholds between North American and Japanese ASD populations and to adjust sagittal modifier thresholds accordingly. METHODS: Retrospective case series of 717 patients with ASD who had baseline radiographs and Oswestry Disability Index (ODI) from North America (n = 518) and Japan (n = 199) were studied. Patients were compared at baseline for ODI, ODI offset from age- and ethnic-specific values (ODIni), and radiographic parameters. RESULTS: Significant differences in classification were observed: A greater proportion of Japanese patients had marked pelvic tilt deformity, whereas a greater proportion of US patients had marked SVA deformity; no difference in the pelvic incidence–lumbar lordosis mismatch sagittal modifier was observed. Health-related quality-of-life scores also differed, with a greater ODI raw value observed in the US patients but similar ODIni scores between cohorts. Stratifying ODIni scores by sagittal modifier grades revealed similar disability scores corresponding to the 0 to + thresholds for pelvic tilt, pelvic incidence–lumbar lordosis mismatch, and sagittal vertical axis across ethnicities. Finally, linear regression analysis demonstrated that compared with US patients, Japanese patients had a lower estimated ODI corresponding to established thresholds of radiographic deformity. CONCLUSION: Our findings demonstrate significant variability in health-related quality-of-life measures and radiographic parameters between North American and Japanese patients, supporting the need for population-adjusted sagittal modifiers to more accurately classify deformity. ABBREVIATIONS: ASD, adult spinal deformity HRQOL, health-related quality of life LL, lumbar lordosis ODI, Oswestry Disability Index ODIni, Oswestry Disability Index need for improvement PCS, physical component summary PI, pelvic incidence PI-LL, pelvic incidence–lumbar lordosis mismatch PT, pelvic tilt SRS, Scoliosis Research Society SVA, sagittal vertical axis TK, thoracic kyphosis